Investigation of the ventilation and thermal performance of mashrabiya for residential buildings in the hot-humid climate of Saudi Arabia - Bagasi, Abdullah Abdulhameed (2022)
The residential sector in Saudi Arabia is the most energy-consuming building sector, accounting for about 50% of the total energy generated. A large proportion of this energy is used to maintain the indoor air temperature at the required comfort level. While the lack of optimal use of natural resources in buildings, such as natural ventilation also contributes to the rising consumption. Traditionally, the Saudi buildings were characterised by different architectural solutions and elements such as the mashrabiya, which was closely related to the local environment and responded to many factors, such as climatic conditions and occupants needs. Mashrabiya is an opening covered with a wooden lattice for ventilation, daylight, privacy, and an aesthetic appeal for houses. Although there are many studies and research on the mashrabiya, most studies addressed either the ventilation or daylight aspect and few included evaporative cooling without conducting field tests or validated modelling to investigate its actual performance and the extent of its impact on the internal thermal environment. Therefore, this research aims to investigate the effect of the mashrabiya on the indoor thermal environment and develop a mashrabiya design to enhance indoor thermal comfort in the residential buildings in hot climates with reference to Jeddah, Saudi Arabiya. The research, besides the literature review, includes field experiments and simulation works. The field experiment results indicated that opening the mashrabiya allowed more airflow into the room and reduced the indoor temperature by up to 2.4 °C compared to the closed mashrabiya. Furthermore, by integrating evaporative cooling strategies (pots, water sprays, and wet cloth) with the open mashrabiya, it was found that the most effective approach to improving the room air temperature was hanging a wet cloth and the average room temperature reduced by up to 6.8°C. Along with that, the thermal mass played a significant role in reducing indoor air temperatures' thermal swings. In order to expand its scope in the study and examination of the mashrabiya, a computational fluid dynamic simulation tool was used. The results of the base case of the mashrabiya in the simulation generally indicated that the slats' inclination plays a vital role in the direction of the airflow into the room, and this is evident with tilting the slats angle to +30 or -30, as the airflow becomes more directed and sharper to the ceiling or the floor. Also, compared to the benchmark case, the mashrabiya contributed to increasing the proportion of airflow into the room. This study also introduced the concept of integrating heat transfer devices into the mashrabiya to reduce the indoor temperature further. Overall, while the outdoor temperature was set at 40 C°, based on the average outdoor temperatures monitored from field experiment measurements during the summer season, the technique has been able to decrease the indoor air temperature by up to 7.5°C (18.8%). This research presents comprehensive theoretical, experimental and computational methods of the evaluation of the performance of the mashrabiya and some strategies used to enhance thermal comfort. It can be summarized from the field studies that integrating evaporative cooling strategies, particularly the cloth strategy with mashrabiya in addition to the thermal mass, contributed to enhancing comfort. It can be concluded from the simulation work that the Ansys Fluent as a CFD tool gave flexibility in allowing testing and analysis of different designs and models, which contributed to a more accurate and better understanding than the fieldwork of the performance and effect of mashrabiya on ventilation, temperature and thermal comfort. In addition, the incorporation of heat transfer devices contributed to enhancing thermal performance and thus the achievement of simulation aim and objectives.